FRK plays an oncogenic role in non‐small cell lung cancer by enhancing the stemness phenotype via induction of metabolic reprogramming. Issue 1 (26th July 2019) - Zhang, Li; Yang, Yongfeng; Chai, Li; Bu, Hong; Yang, Ying; Huang, Hong; Ran, Jingjing; Zhu, Yihan; Li, Li; Chen, Fei; Li, Weimin
Abstract : The role of Fyn‐related kinase (FRK) in malignant tumors remains controversial. Our study investigated the function of FRK in lung cancer. Immunohistochemistry staining and generating a knockout of FRK by CRISPR/Cas9 in H1299 (FRK‐KO‐H1299) cells were strategies used to explore the role of FRK. Immunohistochemistry staining indicated that FRK expression was elevated in 223 lung cancer tissues compared to 26 distant normal lung tissues. FRK contributed to poor survival status in lung cancer patients and acted as a predictor for poor prognosis of lung cancer. Knockout of FRK by CRISPR/Cas9 markedly inhibited proliferation, invasion, colony formation and epithelial–mesenchymal transition (EMT) process in the lung cancer cell line H1299. Further exploration indicated that FRK‐KO damaged the stemness phenotype of H1299 by inhibiting CD44 and CD133 expression. Seahorse detection and a U‐ 13 C flux assay revealed that FRK‐KO induced metabolism reprogramming by inhibiting the Warburg effect and changing the energy type in H1299 cells. Epidermal growth factor stimulation recovered the expression of FRK and biological functions, metabolic reprogramming and stemness phenotype of H1299 cells. FRK plays an oncogenic role in lung cancer cells via a novel regulation mechanism of enhancing the stemness of H1299 cells by inducing metabolism reprogramming, which finally promotes EMT and metastasis. Our study also indicates that FRK could be used as a potential therapeutic target for drug development. Abstract : What's new? Fyn‐related kinase (FRK) was found to act as an important regulatory protein in many malignancies, but its tissue‐specific cellular role remains to be understood. Here, the authors demonstrated the oncogenic role of FRK in lung cancer. Higher expression of FRK contributed to poor survival of lung cancer patients and acted as a predictor for poor prognosis. Mechanistically, knockout of FRK damaged malignant functions by inhibiting the stemness phenotype of lung cancer cells and metabolic reprogramming, which ultimately impaired the epithelial–mesenchymal transition process and metastasis capability. The results highlight FRK as a novel potential therapeutic target for lung cancer treatment.